2x(2×(-4)+(-7)-4 =
(-3)-20+5x(-4-8) =
15-[4x(-5+4)-3]+[32:(-8)] =
Respuestas a la pregunta
Contestado por
1
Explicación paso a paso:
2*(-8-7)-4=2*(-15)-4=-30-4=-34
(-3)-20+5*(-12)=(-3)-20-60=60-60=0
15-(4*(-1)-3)+(-4)=15-(-4-3)-4=15-(-7)-4=15+7-4=22-4=18
Gracias por favor no me reportes
Otras preguntas
Informática,
hace 3 meses
Matemáticas,
hace 3 meses
Historia,
hace 3 meses
Salud,
hace 6 meses
Inglés,
hace 6 meses
Ciencias Sociales,
hace 11 meses
Religión,
hace 11 meses
Historia,
hace 11 meses